Designing of a wide-area power system stabilizer using an exponential distribution optimizer and fuzzy controller considering time delays - Chao Zhang; Xucheng Chang; Jun Dai; Zhiqiang Chen; Manoochehr Babanezhad (Scientific Reports)
Abstract In this paper, explore the effectiveness of a new Wide Area Fuzzy Power System Stabilizer (WAFPSS), optimized using the Exponential Distribution Optimization (EDO) algorithm, and applied to an IEEE three-area, six-machine power system model. This research primarily focuses on assessing the stabilizer’s capability to dampen inter-area oscillations, a critical challenge in power grid operations. Through extensive simulations, the study demonstrates how the WAFPSS enhances stability and reliability under a variety of operational conditions characterized by different communication delay patterns. The application of the proposed stabilizer on this specific IEEE model provides a detailed insight into its performance in real-world scenarios, illustrating its adaptability and effectiveness in managing dynamic disturbances. The simulation results reveal that the proposed WAFPSS achieves significant reductions in the Integral Time Squared Error (ITSE), with improvements of 94.1%, 97.02%, and 98.18% in three distinct cases, showcasing its superior damping capability and robustness. The findings indicate that the advanced optimization techniques provided by the EDO algorithm significantly improve the stabilizer’s response, ensuring robust power system performance. This integration of WAMS with sophisticated control systems using fuzzy logic presents a strategic solution to managing the complexities faced by modern power networks, optimizing their stability in the face of increasing renewable integration and fluctuating demand.